Detection and Diversity of Tetracycline Resistant Bacteria in Fish Ponds of Rajshahi Region - Hafiz, Sharmin; Rahman, M Habibur (Journal of Bio-Science, 2024)
The growth of aquaculture as a key food production industry, particularly in Bangladesh, has led to the increased use of various chemicals and drugs. This study focuses on the critical analysis of bacterial profiles in the waters of fish farming ponds in the Rajshahi district of Bangladesh, a necessary step for disease management and addressing the public health issues related to antibiotic-resistant bacteria. The research found a significant presence of bacteria in these waters, with viable bacterial counts fluctuating from 3.0×10² to 4.2×10³ CFU/ml at a Tetracycline concentration of 32 µg/ml, and 0.5×10² to 1.8×10³ CFU/ml at 64 µg/ml. Using 16S rRNA gene analysis, we discerned a dozen distinct bacterial species spanning six genera that demonstrate resistance to tetracycline. These include Enterobacter asburiae, Aeromonas sp., Acinetobacter sp., Bacillus sp., Bacillus cereus, Enterobacter cloacae, Acinetobacter gandensis, Escherichia coli, Shigella sp., Enterobacter hormaechei, Acinetobacter baumannii, and Bacillus altitudinis. The study underscores the critical need for preventive actions in fish farming to address these resistant bacteria and calls for comprehensive research to trace their origins and pathways of transmission. This research significantly contributes to the understanding of antibiotic resistance in aquatic ecosystems and its broader implications for public health. J. Bio-Sci. 32(2): 23-30, 2024